Lasers, active media : 10-W 4.6-μm quantum cascade lasers. (31st August 2020) - Dudelev, V V; Mikhailov, D A; Babichev, A V; Losev, S N; Kognovitskaya, E A; Lyutetskii, A V; Slipchenko, S O; Pikhtin, N A; Gladyshev, A G; Denisov, D V; Novikov, I I; Karachinsky, L Ya; et al.
Abstract: Ridge quantum-cascade lasers emitting near 4.6 μm are fabricated and their power and spectral characteristics are studied. Stable pulsed lasing with an output optical power exceeding 10 W (more than 5 W from one facet) at room temperature is demonstrated.